Factors associated with pressure ulcers in adults in acute care hospitals. - Fisher, Andrea R. (University of Ottawa (Canada), 1999)
Study aim and objectives. The aim of this analysis is to identify and describe the relationship of factors associated with pressure ulcers, Stage 2 or greater, in adults in acute care hospitals. The objectives are: (1) to develop a model to describe the association of demographic and clinical factors in the presence of pressure ulcers using three years of prevalence data (1993, 1994 & 1995); and (2) sample, namely the 1996 prevalence study. Design. Cross-sectional, prevalence studies. Subjects. All adult inpatients in an acute care, university teaching hospital during one 12 hour day time period. Data were collected mid-week to reflect new admissions, and pre and post-operative cases, and in mid-September to avoid summer and winter seasonal variations. Main outcome measure. Stage 2 or greater pressure ulcers according to the Agency for Health Care Policy and Research Clinical Practice Guidelines, Pressure Ulcers in Adults: Prediction and Prevention (1992) recommendations for staging ulcers. Data collection instruments. Demographic and Clinical Profile Form, Prevalence Grid, and Braden Scale (1987). Sample size. The derivation sample, 1993--95 prevalence studies, included 1,992 subjects and the validation sample, 1996 prevalence study, included 581 subjects. (Abstract shortened by UMI.)
Keywords: Health Sciences, Medicine and Surgery.